Analisis Straregi Pemeliharaan Tanaman Jagung Di Desa Bahalbatu III - Eni Marlina Sihombing; Ibelala Gea (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to provide information about Corn Maintenance Strategies in Bahal Batu III. Corn is a staple food along with rice, and can be used in various dishes as a side dish or snack. Corn not only contains carbohydrates, but also contains enough nutrients and crude fiber as a staple food which has a positive impact on health. Corn is also a substitute food or supplement for humans. Using the right amount of fertilizer will make corn plants grow more optimally. Measuring the growth of productive corn plants by applying various types of compound fertilizer to land in Bahal Batu III village and determining the most suitable type of compound fertilizer for the growth and yield of corn plants on the land. The survey was carried out on the land of Bahal Batu III village. Apart from that, corn can also be used as food for the community and has increased the price of corn consumption in society as a whole. Phosphorus is important for plant growth and yield, playing important roles such as encouraging flower and grain formation and strengthening thatch to prevent dropping and improve quality. The research results showed that even with different complex fertilizer compositions, all the parameters observed were plant height, stem diameter, number of leaves, ear length, ear diameter, number of seeds per row, seed weight per ear, and yield potential.